POTENSI SUMBERDAYA MATA AIR ALAMI KOMPLEKS AWAR-AWAR SUMAMPIR UNTUK PERENCANAAN SUMBER AIR BERSIH PEDESAAN POTENCY OF WATER SPRING RESOURCES AT AWAR-AWAR COMPLEX, SUMAMPIR, FOR DESIGNING RURAL CLEAN WATER RESOURCES - , Nastain; Hardini, Probo (Pembangunan Pedesaan, 2005)
This research was conducted to know quality potential, discharge, and flowing energy of water spring of Kompleks Awar-awar Sumampir Purwokerto Utara located at rural upper end for designing rural clean water resources. Variables observed were physical and chemical water quality, need of water, discharge of the spring, and flowing energy. The result of research showed that water quality of the spring was suitable for clean water resources and drinking water resources of rural, with average discharge of water was 4.07 liter/s so it could be used to fulfill the clean water requirements of the Sumampirâs people who were not served by PDAM for 16 years (100% people), 27 years (75% people), and 37 years (60% people), and based on energy potential, available gravitation flowing system could be used if pipe minimum diameter of 3 inch was used.